75.3k views
10 votes
Solve the system of equations using substitution

3x – 2y = 3 –4x + y = 6

(X,Y)= (? ,?)

User Dave Brown
by
5.1k points

2 Answers

8 votes

Answer:

(-3,-6)

Explanation:

User Marc Audet
by
5.2k points
12 votes

Explanation:

I hope this helps.........

Solve the system of equations using substitution 3x – 2y = 3 –4x + y = 6 (X,Y)= (? ,?)-example-1
User Tbielaszewski
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.